Negative Impoliteness in “Ellen DeGeneres” Talk Show: Pragmatic Approach - Wendy Wendy; Ambalegin Ambalegin (Institut Agama Islam Negeri Palopo, 2022)
This research is using pragmatic study to observe the types of negative impoliteness based on the talk show